PERIODIZATION IN BASKETBALL: EVIDENCE VS./FOR REAL LIFE - Jukic, Igor (Sport- és Egészségtudományi füzetek, 2025)
Periodization of sports preparation implies systematic planning and programming of training, competition and re-covery in time cycles that are specific in terms of content, workload and training methods. The fundamental goals of periodization in basketball are the protection of player health (ensuring availability for training and competition) and improving competitive performance. At each of these competitions, basketball teams should be in optimal sports shape. The special feature of achieving peak performance in basketball is related to a large number of potential peaks, and it is often difficult to predict which games during the competitive season will be particularly important in terms of results. A special obstacle to the implementation of ade-quate periodization strategies is the congested competition schedule during the competition season. Such a competi-tion system puts coaches in a situation to choose between short-term (microcycles) and long-term approaches (macro-cycles) to planning and programming.